The Strategic Leadership Role of the Principal in the Implementation of Holistic Integrative Early Childhood Services at TK Islam Silmi Samarinda - Aslindah, Andi; Brantasari, Mahkamah; Pratiwi, Yuni Ika; Meyssi, Monika; Mailina, Mailina (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to explore the vital role of the school principal in implementing Holistic Integrative Early Childhood Education (PAUD HI) services at TK Islam Silmi Samarinda. The PAUD HI approach emphasizes the integration of education, health, nutrition, parenting, child protection, and child welfare services. In this context, the principal plays a central role in coordinating and synergizing these various components to ensure that children's basic needs are met comprehensively and optimally.This research employs a descriptive qualitative approach, using data collection techniques such as in-depth interviews, participatory observation, and document analysis. The findings reveal that the principal acts as an instructional leader, integrative program manager, and facilitator of cross-sector collaboration. Strategies implemented include participatory planning based on children's needs, collaborative program execution with external partners such as community health centers and child protection agencies, as well as periodic evaluations grounded in collective reflection. Challenges identified include limited human resources, variations in parenting styles, and the socio-economic conditions of parents. The principal demonstrates adaptive leadership by formulating locally grounded solutions. These findings affirm that the success of PAUD HI implementation heavily depends on strategic leadership and the ability to establish sustainable partnerships. This study contributes to a deeper understanding of leadership practices in early childhood education based on a holistic and integrative approach.